2011
DOI: 10.1063/1.3613927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact doping in superlattice-based minority carrier unipolar detectors

Abstract: We report the influence of the contact doping profile on the performance of superlattice-based minority carrier unipolar devices for mid-wave infrared detection. Unlike in a photodiode, the space charge in the p-contact of a pMp unipolar device is formed with accumulated mobile carriers, resulting in higher dark current in the device with highly doped p-contact. By reducing the doping concentration in the contact layer, the dark current is decreased by one order of magnitude. At 150 K, 4.9 μm cut-off devices e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…For this purpose, a laser source can be used [8][9] providing the responsivity at a given wavelength. Here we preferred to use blackbodies (BBs) [2,[10][11], which are more representative of the operational conditions, in terms of spectral bandwidth as well as in terms of incident power.…”
Section: Current Under Illumination Measurementmentioning
confidence: 99%
“…For this purpose, a laser source can be used [8][9] providing the responsivity at a given wavelength. Here we preferred to use blackbodies (BBs) [2,[10][11], which are more representative of the operational conditions, in terms of spectral bandwidth as well as in terms of incident power.…”
Section: Current Under Illumination Measurementmentioning
confidence: 99%
“…By using the M-structure SL as a barrier region, the band alignments can be experimentally controlled, allowing for efficient extraction of photocurrent under applied biases of less than 50 meV [22]. It has been demonstrated that the dark current in a pMp detector can be decreased by an order of magnitude by reducing the doping concentration in the contact layer [96].…”
Section: M-structurementioning
confidence: 99%
“…Most of these progresses were obtained by the use of particular device designs using nBn 9 , C-BIRD 12 or pMp 13,14 structures, not by the choice of the InAs/GaSb SL period while, paradoxically, the SL period composition governs the material properties of the active zone material. In order to exhibit MWIR operation, most of the SL periods reported are symmetric (InAs to GaSb thickness ratio close to one) with thicknesses in the range of 8 to 11 monolayers (MLs) [2][3][4][5][6][7][8][9][10][11][12]15 .…”
Section: Introductionmentioning
confidence: 98%